Screen Transversal Lightlike Submanifolds of Indefinite Kenmotsu Manifolds - Gupta, Ram Shankar; Sharfuddin, A. (Sarajevo Journal of Mathematics, 2024)
In this paper, we introduce screen transversal lightlike submanifolds of indefinite Kenmotsu manifolds. We obtain a characterization of screen transversal anti-invariant lightlike submanifolds as well as a condition for induced connection to be a metric connection and provide an example of ST-anti-invariant lightlike submanifold of R^9_2. Also, we obtain necessary and sufficient conditions for radical screen transversal lightlike submanifolds to be totally geodesic. 2000 Mathematics Subject Classification. 53C15, 53C40, 53C50, 53D15